2011
DOI: 10.1021/jo201658y
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Based Reaction Screening: Tandem Retro-Diels–Alder/Diels–Alder Cycloadditions ofo-Quinol Dimers

Abstract: We have accomplished a parallel screen of cycloaddition partners for ortho-quinols utilizing a plate-based microwave system. Microwave irradiation improves the efficiency of retro-Diels-Alder/Diels-Alder cascades of ortho-quinol dimers which generally proceed in a diastereoselective fashion. Computational studies indicate that asynchronous transition states are favored in Diels-Alder cycloadditions of ortho-quinols. Subsequent biological evaluation of a collection of cycloadducts has identified an inhibitor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
(86 reference statements)
2
25
0
Order By: Relevance
“…However, only a small amount of product 19h was isolated (entry 8), presumably due to the multiple reaction sites for the generated cyclopentadienone intermediate. In all cases, reactions to form [4+2] adducts proceeded in high diastereoselectivity which was in accordance with previous observations in our synthesis of chamaecypanone C. 5a Endo -selectivity and facial-selectivity align well with the observed reactivity of o -quinols, 35 wherein the bulky aromatic substituents are oriented away from the sterically demanding quaternary center.…”
Section: Resultssupporting
confidence: 90%
“…However, only a small amount of product 19h was isolated (entry 8), presumably due to the multiple reaction sites for the generated cyclopentadienone intermediate. In all cases, reactions to form [4+2] adducts proceeded in high diastereoselectivity which was in accordance with previous observations in our synthesis of chamaecypanone C. 5a Endo -selectivity and facial-selectivity align well with the observed reactivity of o -quinols, 35 wherein the bulky aromatic substituents are oriented away from the sterically demanding quaternary center.…”
Section: Resultssupporting
confidence: 90%
“…150 Moreover, (−)- 97 does not display inhibition of HIF-2, NF-κB, or SRE dependent transcription at the same concentration. However, during the experiments in the NCI 60-cell screen at 10 μM, (−)- 97 did not pass the threshold for further evaluation of cell growth inhibition.…”
Section: Development Of Small Molecules Targeting Ap-1mentioning
confidence: 97%
“…Dong et al recently reported an interesting MW-assisted parallel reaction screening for evaluation of the Diels-Alder cycloaddition of o-quinol dimers in order to identify reactive reaction partners and bioactive compounds [98]. The reaction between o-quinol dimers (252) and various dienes or dienophiles under MW activation led to bicyclo[2.2.2]octenones (253/254) via retro-[4 + 2]-followed by [4 + 2]-cycloaddition with external dienophiles (Scheme 17.43).…”
Section: Intermolecular Diels-alder Reactionsmentioning
confidence: 99%
“…The nonthermal MW effects, demonstrated by the absence of reaction products when the reactions were carried out under conventional heating conditions, were explained by considering the development of polarities between ground state and transition state generated from PM3 calculations of the dipole moments of reagents, products, and transition states[41].Willy et al developed the synthesis of 3,4,5-substituted isoxazoles (102) by a one-pot, three-component reaction pathway[42]. Alkynyl ketones (100) (Scheme 17.13), obtained by coupling of acid chlorides(98) with terminal alkynes…”
mentioning
confidence: 99%